Pendampingan Pelaksanaan Sholat Wajib Santri Melalui Film Edukasi di TPQ/TQA Masjid Muhajirin Air Dingin Padang - Juandi Pasaribu JU (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2024)
This accompaniment is blamed by the lack of consciousness of the TPQ/TQA of the Muhajirin mosque to perform the five-time prayer, the deterioration of the righteousness and worship of the santri resulting in the usual abandonment of the prayer and will get a great sin and the relationship to God will be bad even social relations both the family environment, the community and the school centers. This addition aims to educate the implementation of 5 times and values of education character centri such as worship and morals in everyday life through educational film at TPQ/TQA mosque Muhajirin Water Cold Padang. This method is performed in several stages, the initial stages give a general overview of the implementation of the five-time prayer, then show the film Religious Editing in particular the execution of the fifth-time prayers, and the final stages emphasize and customize the centurion so that the prayer is made as a necessity. This activity was followed by 30 people of the TPQ/TQA and carried out with observation activities of satisfaction of the center, the ability to perform prayers compulsory sholat. The accompanying results show that through religious education films can improve the implementation of the compulsory sholat. Children's awareness develops into religious values, higher worship, better morality, character, good understanding of each other, consciousness of prayer without having to be commanded, this is because it has been emptied by the activity of the environment that is embedded in the soul of the centurion.